WRB is the receptor for TRC40/Asna1-mediated insertion of tail-anchored proteins into the ER membrane - Vilardi, Fabio; Lorenz, Holger; Dobberstein, Bernhard (Journal of cell science, 2011)
Tail-anchored (TA) proteins are post-translationally targeted to and inserted into the endoplasmic reticulum (ER) membrane through their single C-terminal transmembrane domain. Membrane insertion of TA proteins in mammalian cells is mediated by the ATPase TRC40/Asna1 (Get3 in yeast) and a receptor in the ER membrane. We have identified tryptophan-rich basic protein (WRB), also known as congenital heart disease protein 5 (CHD5), as the ER membrane receptor for TRC40/Asna1. WRB shows sequence similarity to Get1, a subunit of the membrane receptor complex for yeast Get3. Using biochemical and cell imaging approaches, we demonstrate that WRB is an ER-resident membrane protein that interacts with TRC40/Asna1 and recruits it to the ER membrane. We identify the coiled-coil domain of WRB as the binding site for TRC40/Asna1 and show that a soluble form of the coiled-coil domain interferes with TRC40/Asna1-mediated membrane insertion of TA proteins. The identification of WRB as a component of the TRC (Get) pathway for membrane insertion of TA proteins raises new questions concerning the proposed roles of WRB (CHD5) in congenital heart disease, and heart and eye development.
Gesehen am 08.12.2022